PCR detection of the crayfish plague pathogen in narrow-clawed crayfish inhabiting Lake Eğirdir in Turkey - Svoboda, J; Kozubíková, E; Kozák, P; Kouba, A; Bahadir Koca, S; Diler, O; Diler, I; Policar, T; Petrusek, A (Diseases of aquatic organisms, 2012)
Many populations of the narrow-clawed crayfish Astacus leptodactylus in Turkey, including those inhabiting Lake Eğirdir, declined drastically in the mid-1980s due to introduction of crayfish plague Aphanomyces astaci. However, unlike many other localities, there has been some recovery in the A. leptodactylus population inhabiting this lake even though crayfish plague has been suspected to have persisted since then. In support of this, DNA from 5 of 34 healthy-looking crayfish sampled recently from the lake tested positive by both conventional and real-time PCR using species-specific primers targeting the rDNA internal transcribed spacer region, and product sequence analysis confirmed the identification of A. astaci. This complies with other recent reports of coexistence of native European crayfish with this pathogen, and further research is now needed to identify the key mechanisms allowing it.
Keywords: Turkey; Population Density; polymerázová řetězová reakce; Turecko; hustota populace; severní raci; Astacoidea; Animals; zvířata; Polymerase Chain Reaction; Lakes; jezera